Didactic strategies and meaningful learning in Master of Education Management students and University teaching of a faculty education of Lima - Quiñones Rodríguez, Sonia (2019)
This research seeks to describe and explain the relationship between teaching strategies and meaningful learning in students of Master of Management of Education and University Teaching 2017-I School of Education UNMSM. The selection of the study sample was made through the technique of simple random sampling. The type of research was basic descriptive, explanatory non-causal relational, the design of the research was non-experimental. For the analysis of data, the Inferential statistics was used and for the processing of the information the statistical program SPSS Version 24 and the Pearson Correlation were used. Results: The Pearson Correlation Coefficient r = 0.56 approximately represents 56% of the data are linearly related between the didactic strategies and the significant learning in the students of. Master of management of education and university teaching 2017-I of the Faculty of Education UNMSM. The results indicated that there is a linear relationship between teaching strategies and meaningful learning in students of the Master of Management of Education and University Teaching 2017-I of the Faculty of Education UNMSM. Therefore the didactic strategy the seminar has a greater direct relation with the significant learning.